Apostate’s rules from the perspective of Al- Zulmi as a fundamentalist approach - Ayad Kamil Ibrahim Al-Zeebaree (Research Journal in Advanced Humanities, 2023)
This research is a modest contribution to studying the provisions of the apostate from the perspectives of Al-Zulmi fundamentalist approach, which aims to study Islam strife against anti-crime, the basis of punishment and its purpose in Islamic law, and the rule of the apostate in the Quran and Sunnah and the killing of the apostate in Fiqh, the views of contemporary scholars and the opinion of Dr. Zulmi on the killing of the apostate is fundamentalist approach. Islamic law is interested in combating and fighting crimes on the religious and secular side together. Islam has self-purified of vices and corruption by the self-knowledge and worship of Allah Almighty. Islam has educated self to love justice and good and hate injustice and Evil. Conscience education is the first basis in preventing crime, and punishment in Islamic law is based on mercy and justice. It is Allah's mercy to his slaves that the punishment is legislated for anyone who is not on the right path. The punishment in Islamic law is to prevent the crime before it occurs, and to achieve the infidelity after it occurs. One of the crimes committed by human being towards himself apostasy. Quran has mentioned apostasy in the sense of leaving Islam explicitly more than once, and repelling apostasy and its people in this world and the Hereafter, but they differed in the estimation of a worldly punishment. It is reasonable to assume that there is no worldly punishment because it falls within the freedom of thought and freedom of belief except leaving the Islamic regime, its security and corrupting in earth. As for the narrations that indicate the criminalization of apostasy and the killing of the apostate, leaving the religion has been compared with leaving the group. The absolute narratives are restricted according to the general rule of fundamentalism, and the rule of killing the non-warrior apostate is the ruling on what Allah has not mentioned to the prophet and the prophet did not apply in his life nor his beloved companions.